Acyl pyrazole sulfonamides as new antidiabetic agents: synthesis, glucosidase inhibition studies, and molecular docking analysis - Ahmed, Atteeque; Zaib, Sumera; Bhat, Mashooq Ahmad; Saeed, Aamer; Altaf, Muhammad Zain; Zahra, Fatima Tuz; Shabir, Ghulam; Rana, Nehal; Khan, Imtiaz (Frontiers in Chemistry, 2024)
Diabetes mellitus (DM) is a multi-systematic chronic metabolic disorder and a life-threatening disease resulting from impaired glucose homeostasis. The inhibition of glucosidase particularly α-glucosidase could serve as an effective methodology in treating diabetes. Attributed to the catalytic function of glucosidase, the present research work focuses on the synthesis of sulfonamide-based acyl pyrazoles (5a-k) followed by their in vitro and in silico screening against α-glucosidase. The envisaged structures of prepared compounds were confirmed through NMR and FTIR spectroscopy and mass spectrometry. All the compounds were found to be highly potent against α-glucosidase than the standard drug, acarbose (IC50 = 35.1 ± 0.14 µM) with IC50 values ranging from 1.13 to 28.27 µM. However, compound 5a displayed the highest anti-diabetic activity (IC50 = 1.13 ± 0.06 µM). Furthermore, in silico studies revealed the intermolecular interactions of most potent compounds (5a and 5b) with active site residues reflecting the importance of pyrazole and sulfonamide moieties. This interaction pattern clearly manifests various structure-activity relationships while the docking results are correspondent with the IC50 values of tested compounds. Hence, recent investigation reveals medicinal significance of sulfonamide clubbed pyrazole derivatives as prospective therapeutic candidates for the treatment of type 2 diabetes mellitus (T2DM).